Adubação nitrogenada de sistema e ofertas de forragem sobre a produtividade de um sistema de integração lavoura-pecuária - Carvalho, Acir Felipe Grolli (2018)
In recent years, Brazil has prioritized the use of production systems that opt to consider besides the higher productivity also the environmental issue. With this, the Crop-Livestock system has been gaining space, enabling plant and animal production in the same place. In this case, there are many studies that evaluate the different herbage allowances in the Crop-Livestock system, in addition to nitrogen fertilization, but allies can promote productive gains in the same. The objective of the present work was to evaluate the responses of different herbage allowance and N application times in the long - term Crop-Livestock system. The work carried out in Agropecuária Pachecho dependencies in the municipality of Abelardo Luz-SC during the year 2015 under Cfb climate and soil classified as typical dystrophic Bruno Latossolo. The experimental area was conducted under Crop-Livestock system system from 2012. The experimental design was a randomized block design in a 2x2 factorial scheme with three replicates. The first factor was herbage allowance (HA and LA) and the second factor was composed of two nitrogen fertilization periods (NP - N applied to pasture, NG - N applied to grains). This work evaluated the crops in succession of ryegrass, corn silage and Rioja bean. The results were analyzed through the Genes program. The use of grasses as ryegrass is shown to be feasible in Crop-Livestock system, providing increases in productivity of properties that adopt this system. The supply of forage are the most important factors to be observed, this has a direct relationship with forage production, structural composition and animal performance and behavior. In addition, another factor that obtained better answers were the treatments that received nitrogen fertilization in the pasture. Presenting greater responses of the plant and animals to the applied nitrogen. In the treatment that was managed with high herbage allowance and that received nitrogen fertilization, there was greater production of pasture and animal production. In turn, silage production was affected only by the herbage allowance of ryegrass. The second harvest beans had no difference between the treatments for their production, showing efficient fertilization only in the pasture.